Alterations of the skin microbiome in multiple system atrophy: a pilot study - Daji Chen; Lang Sun; Linlin Wan; Zhao Chen; LinLiu Peng; Jinzi Peng; Riwei Ouyang; Xiafei Long; Kefang Du; Xiao Dong; Xiaokang Wu; Xinying Xiao; et al. (npj Parkinson's Disease)
Abstract Multiple system atrophy (MSA) alters skin physiology, potentially impacting skin microbiota. This pilot study investigated whether skin microbiota differs in MSA and whether these differences relate to disease severity. Using 16S rRNA sequencing of cervical and axillary sites in MSA, Parkinson’s disease, and controls, we identified distinct microbial patterns among groups. These patterns allowed cohort classification and showed strong associations with clinical symptoms, suggesting disease-related microbial alterations in MSA.